Identifikasi Dan Pengembangan Kriteria Rencana Pemindahan Lokasi Pusat Perkantoran Kota Pekanabru Berdasarkan Ahp (Analytical Hierarchy Process) - Ari Sandhyavitri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
As a form of equitable development efforts, Pekanbaru city government plans to move the centre of Pekanbaru city office. In this study, there are 3 alternative locations of removal plans of central office of Pekanbaru city. Those locations are Jalan Palembang Kelurahan Kulim Kecamatan Tenayanraya, Jalan Badak Kelurahan Sail Kecamatan Tenayanraya, and Jalan Lingkar Luar KIT Kelurahan Okura Kecamatan Rumbai Pesisir. This study identifies the criterion used in choosing the location of central office of Pekanbaru city, pursuant to physical criteria, accessibility criteria, infrastructures criteria, and environmental criteria. Therefore supporting system used in this analysis is Analytical Hierarchy Process (AHP) of which result will be corrected by using Expert Choice programme.  The results of the AHP analysis obtained the significant criteria are: accessibility criteria (42,5%) and the next physical criteria (28,2%), infrastructures criteria (21,3%), and environmental criteria (8,0%). As for the most optimal alternative location for new government office center of Pekanbaru city are: Jalan Badak, Tenayanraya (43,5%), Jalan Palembang, Tenayanraya (42,0%), and Jalan Lingkar Luar KIT, Okura (14,5%). Subcriteria which mostly influencing the choice of location in Jalan Badak are: cost of transportation, duration to the location, and availability of electrical power networks.  Keywords: Analytical Hierarchy Process (AHP), Expert Choice, Priority.